(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2005)
The objective of this paper is to describe some acceptance based procedures to the treatment of exhibitionism. The client was a 24 years old student, who looked for psychotherapic treatment spontaneously. He had been showing exhibitionists responses for eight years. His exhibitionist responses used to occur once a day followed by masturbation and uncomfortable feelings of guilt-according to the self-records of the first twenty days in treatment. Sixteen sessions were conducted and at the end of them, the masturbation, the paraphiliac thoughts and the public exhibition had their frequency reduced to no occurrence in two weeks. This paper discusses the acceptance-based procedures to the treatment of exhibitionism, as well as the relevance of a friendship to promote this particular clinical change.